Geopolymers as a potential material for preservation and restoration of Urban Build Heritage: an overview. Issue 1 (December 2020) - Pagnotta, Stefano; Tenorio, Anna Lluveras; Tinè, Maria Rosaria; Lezzerini, Marco
Abstract: Since the introduction of the term 'geopolymer' by Davidovits in 1978, many works have been published, sometimes providing clear and concise indications, and other times creating confusion about what are a geopolymer. What seems interesting beyond the terminology discourse is the advantage of low CO2 emissions, the use of waste industrial byproducts in their implementation and the resistance to air pollution and aggressive agents. Playing on the combination of the different precursors and alkaline activators, geopolymers can reach competitive mechanical properties and significant environmental benefits. The materials, with specially designed formulations, can be fireproof, breathable, resistant to rising salts and acid rain, as well as products with low emission of carbon dioxide. Furthermore, a further advantage is the ability to imitate natural, artificial and stone materials. There are hundreds of papers about characteristics, properties both of precursors and final product, but only a few of them about the Cultural Heritage Application. Despite this, the data shown by the few publications present to date give hope for a use of these materials for the consolidation, conservation and restoration of the heritage built within the historical centres, where the low CO2 emissions and the characteristics shown by the geopolymers could bring a huge benefit to the environment and the protection of the structures themselves. In this work, we briefly review the bibliography available on the applications of these materials to Cultural Heritage, hypothesising future uses aimed at specific urban contexts, where the application could play a key role in the future projects to restore the built heritage.